Pendampingan Anak menggunakan Pendekatan Agama dalam Pembentukan Perilaku Sosial Remaja di LKSA Nurusyifa Bandung - Zahra, Bilqis Siti (Politeknik Kesejahteraan Sosial Bandung, 2024)
Adolescence is one of the toughest transitions in life. Changes that occur in adolescents are not only in their physical condition but simultaneously in social, cognitive, language, and creative development. So with the changes that occur in adolescence, it is vulnerable to the emergence of social problems caused by low emotional maturity, not only in the low emotional maturity which ultimately impacts social problems in adolescents. But also, the development of a person's religious life is in line with his physical and spiritual development, adolescents need to get assistance in gaining religious awareness which will become a basis for life in social behavior in society. In the process of forming adolescent social behavior using a religious approach is one of the most important elements. This research is entitled